MAKNA ‘INDAH’ LUKISAN ‘KEBAKARAN HUTAN’ RADEN SALEH SEBAGAI PERLAWANAN KONSEP PEMIKIRAN ‘MOOIE INDIËM' - Krisnambudi, Dionisius; Habsari, Sri Kusumo; Farhah, Eva (UI Scholars Hub, 2026)
The concept of